2013
DOI: 10.3136/fstr.19.849
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonic Marinating on the Transport of Acetic Acid and Salt in Anchovy Marinades

Abstract: In this study, the effect of ultrasonic marinating on the transport of acetic acid and salt in anchovy marinades was investigated. Anchovy fillets were immersed in marinating solution containing 4% acetic acid and 8% salt and treated with static marinating or with 20 kHz ultrasound at different ultrasonic intensity (20, 25 and 30 W/cm 2 ) and at different times (10, 20 and 30 min). In general, the ultrasonic marinating affected moisture transport in anchovy marinades and moisture content decreased while ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Although previous measurements noted some differences, there was a uniform distribution of sodium chloride in all treatments during the ripening stage. Furthermore, Turhan et al [29] studied the effect of US-assisted marination (20 kHz with 20, 25, and 30 W/cm 2 ) on the transport of acetic acid (4 and 8%) and salt in anchovy marinades. The authors showed that the moisture content decreased as the US intensity increased.…”
Section: Preferences Of Consumers Of Ultrasonicated Meatmentioning
confidence: 99%
“…Although previous measurements noted some differences, there was a uniform distribution of sodium chloride in all treatments during the ripening stage. Furthermore, Turhan et al [29] studied the effect of US-assisted marination (20 kHz with 20, 25, and 30 W/cm 2 ) on the transport of acetic acid (4 and 8%) and salt in anchovy marinades. The authors showed that the moisture content decreased as the US intensity increased.…”
Section: Preferences Of Consumers Of Ultrasonicated Meatmentioning
confidence: 99%
“…Beyond the negative effects of slow salt uptake on meat quality, long duration of brine salting of meat can also prove expensive in terms of reduced productivity and yields, impact negatively in terms of space utilisation and have maintenance costs due to the corrosiveness of the brine. Furthermore, besides an interest among processed meat manufacturers in speeding up the uptake of salt in meat, achieving uniform salt profiles in meat is also desirable for a processed meat product (Turhan et al, 2013). Therefore, processed meat manufacturers are in constant search for alternative salting processes that are faster and more efficient, which allow homogeneous salt distribution in meat, would reduce processing time and improve the quality of the product.…”
Section: Introductionmentioning
confidence: 99%
“…For example, González‐González et al () reported a higher homogeneity of sodium distribution along bovine m. longissimus dorsi when marinated with ultrasound assistance for 60 min. There is a growing interest among meat processors to accelerate salt absorption and homogenize profiles in meat (Turhan, Saricaoglu, & Oz, ). The interest is to increase organoleptic characteristics, shelf life, and yields.…”
Section: Introductionmentioning
confidence: 99%